Histopathology Reporting Guidelines for Surgical Cancer - Allen, Derek C. (Springer London : Imprint: Springer, 2013)
This book provides an easily comprehensible and practicable framework for standardised histopathology reports in surgical cancer. It details the gross description, histological classification, tumor differentiation, extent of local tumor spread, involvement of lymphovascular channels, lymph nodes and excision margins of the common carcinomas and also summarises non-carcinomatous malignancies. The 7th edition TNM and WHO classifications of cancers are incorporated, with comments on any associated pathology, diagnostic clues and prognostic criteria. Staging information is supplemented visually by line diagrams. Each chapter has a more formal introductory paragraph than in the previous edition, giving epidemiological, clinical, investigative and treatment summary details, and chapter references are updated; specimen type notes new clinical procedures. Other pathology includes updated immunophenotypic expression with use of new antibodies and molecular techniques. The impact of these ancillary investigations on diagnosis, and as biomarkers of prognosis and prediction of response to treatment is summarised. The effect of adjuvant treatments on cancers is also noted. Experience based clues are given throughout as aids to tumor typing, grading, staging and gauging prognosis and response to treatment. The key information in this book equips the pathologist to produce high quality, clinically appropriate histopathology reports, and to participate in contemporary multidisciplinary team management of patients with surgical cancer. Histopathology Reporting: Guidelines for Surgical Cancer, Third Edition is invaluable for trainee and consultant diagnostic histopathologists all over the world.